HUBUNGAN HUKUM PIDANA ADAT DAN FILSAFAT HUKUM - M Chairul Idrah; Nuraini Nuraini; Siti Nur Ambarini (Legalitas: Jurnal Hukum, 2021)
The purpose of writing this scientific paper is to explain and analyze the relationship between customary criminal law and legal philosophy with normative juridical methods. The existence of additional criminal provisions in the Draft Criminal Code Draft in the form of customary criminal law, the study sees from the philosophy of law in the form of an in-depth and speculative study that customary criminal law which is juridically not recognized as positive law because it does not meet the four requirements for recognizing customary law from an indigenous community unit as a positive law so that it is found that customary law in its field is broad.